The Causes, Effects and Countermeasures of the Eurozone Sovereign Debt Crisis: An In-Depth Analysis from the Perspective of Exchange Rate Fluctuations - Wang, Kaiyue (Asia Pacific Economic and Management Review, 2024)
Since 2009, the eurozone sovereign debt crisis has become the focus of global economic attention. This crisis has not only profoundly affected the economic stability and development of the eurozone, but also had a broad impact on the global financial market. From the perspective of exchange rate fluctuations, this paper will deeply analyze the causes, effects and coping strategies of the eurozone sovereign debt crisis, aiming to provide new perspectives and ideas for understanding the crisis.